Continuous debridement combined with short-term posaconazole therapy for cutaneous mucormycosis caused by Rhizopus oryzae infection secondary to acute myeloid leukemia: a case report - Wang, Fengming; Li, Jv; Xie, Yilian; Ye, Jiayuan (Frontiers in Medicine, 2024)
Cutaneous mucormycosis is a rare fungal infection marked by skin abscesses, swelling, necrosis, dry ulcers, and eschars. Though less fatal compared to other mucormycosis forms, delayed diagnosis and treatment in immunocompromised patients can cause the infection to spread to vital organs, becoming life-threatening. We report a case of lower extremity cutaneous mucormycosis secondary to acute myeloid leukemia, successfully managed with sustained surgical debridement and short-term oral posaconazole. This case highlights the effectiveness of surgical debridement and the potential for short-course antifungal therapy in managing cutaneous mucormycosis.